Eco-friendly methoximation of aromatic aldehydes and ketones using MnCl 2.4H 2 O as an easily accessible and efficient catalyst - Ontivero, Melina C. (2021)
Methoximes are important as a class of intermediates and products, among fine chemicals and specialties. The development of a new, facile and efficient method for their synthesis is reported. The methoximes were properly accessed from the corresponding aromatic aldehydes and ketones in good to excellent yields, under mild conditions, employing the inexpensive and environmentally friendly MnCl 2.4H 2 O as a catalyst (at low loading and without the addition of ligand), in EtOH at 50°C. The scope of the process was systematically assessed.